148k views
18 votes
What is the result of adding these two equations?
-52 - 9y = 3
5.2 - 9y = -2

User AndreasM
by
5.9k points

2 Answers

7 votes

Answer:

-18y = 46.8

Explanation:

Adding Left hand side elements together as well as right hand side

Eq1 = equation 1

Eq2 = equation 2

LHS(left hand side of the equation)

RHS(right hand side of the equation)

LHS of Eq1 + LHS of Eq2 = RHS of Eq1 + RHS of Eq2

-52 -9y + 5.2 -9y = 3 - 2

=> -9y -9y - 52 + 5.2 = 1

=> -18y - 46.8 = 1

=> -18y - 46.8 = 0

=> -18y = 46.8

User Danilo Cabello
by
6.1k points
8 votes

Answer:

5.7-18y=1

Explanation:

52-9y=3

5.2-9y=-2

or,57.2-18y=1

User Vielkind
by
5.7k points